Producción agrícola en el cantón Quevedo y su incidencia en el desarrollo agropecuario de la provincia de Los Ríos periodo 2012-2014 - Mendoza Holguin, Tairo Alfredo (2016)
This research project was conducted in Quevedo Canton and its rural parishes La Esperanza, San Carlos and Quevedo. Farming in the province of Los Rios and its cantons is the main source of production in the province. The fertile land creates favorable conditions for agriculture, livestock and forestry development especially for short cycle crops: as corn, soybeans, passion fruit and perennial crops: cocoa, banana, oil palm, tropical fruits, vital products for the economy of the sector and generating jobs, foreign exchange, food and raw materials for the food industry in the region and the country. These activities to better agricultural productivity are complemented with other technical assistance, fertilizer, certified seed, use of machinery. Importantly, in these areas there is little help from the public and private sectors especially in technical assistance and financing. Thus it was detected in the analysis of information required for this work. The province ranks first in the production of cocoa, passion fruit and compared to African palm production is second only to Esmeraldas. Quevedo Canton and its rural parishes, according to the analysis of this work, has a high percentage of contribution, especially in cocoa and passion fruit, where the level of productivity is good as well as the sale of their products. The results of the investigation shows that the cultivation of cocoa which is mostly available to farmers in the three parishes of the canton Quevedo representing 37% with respect to the remaining crops investigated. On the other hand it can be seen that the low Quevedo Canton productive contribution to the province because there, according to the information analyzed, the little support from lenders and technical assistance from both public and private companies.